2002
DOI: 10.1046/j.1469-8137.2002.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of plant roots by egg‐parasitic and nematode‐trapping fungi

Abstract: Summary• The ability of the nematode-trapping fungus Arthrobotrys oligospora and the nematode egg parasite Verticillium chlamydosporium to colonize barley ( Hordeum vulgare ) and tomato ( Lycopersicum esculentum ) roots was examined, together with capability of the fungi to induce cell wall modifications in root cells.• Chemotropism was studied using an agar plate technique. Root colonization was investigated with light microscopy and scanning electron microscopy, while compounds involved in fungus-plant inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 29 publications
7
112
1
5
Order By: Relevance
“…The plasticity of infection structures in nematode-trapping fungi has been extensively studied in A. oligospora (68). Hence, this fungus has the capacity to colonize plant roots by the aid of appressorium-like structures (69). Furthermore, it was observed that the infected plant cells contained structures similar to the infection bulbs that the fungus forms inside penetrated nematodes (3).…”
Section: Cell Surface Proteins (I) Proteins Containing the Wsc Domaimentioning
confidence: 99%
“…The plasticity of infection structures in nematode-trapping fungi has been extensively studied in A. oligospora (68). Hence, this fungus has the capacity to colonize plant roots by the aid of appressorium-like structures (69). Furthermore, it was observed that the infected plant cells contained structures similar to the infection bulbs that the fungus forms inside penetrated nematodes (3).…”
Section: Cell Surface Proteins (I) Proteins Containing the Wsc Domaimentioning
confidence: 99%
“…Another type of plant protection mediated by endophytic fungi may come from nematophagous fungi which can inhabit plant roots as endophytes (Bordallo et al, 2002). In a similar fashion, some species of entomophagous fungi [e.g.…”
Section: Interactions With Nematodesmentioning
confidence: 99%
“…In this case, the dye must be applied before removal of paraffin (Ruzin, 1999). This method allows the detection of phenolics as well as tannins, lignins and suberins (Baayen et al, 1996;Bordallo et al, 2002;Mellersh et al, 2002;Crews et al, 2003). It also works well as a general staining but combined with other microscopical techniques can give valuable information (LozanoBaena et al, 2007;Pérez-de-Luque et al, 2007).…”
Section: How Are Resistant Plants Identified? the Breadth Of Techniqumentioning
confidence: 99%